Genetic profiling -- implications for refined diagnosis: and treatment of soft tissue sarcomas. - Carneiro A; Nilbert M (Acta Orthopaedica (Supplement))
Soft tissue sarcomas (STS) are challenging as they represent a morphologically and genetically heterogeneous groups of tumors. A multitude of genetic changes, often in the form of fusion genes, were recognized during the 1980's and now constitute a diagnostic lexicon in several STS subtypes, whereas many of the more common subtypes are genetically complex without distinct alterations. Refined STS management requires improved diagnostic reproducibility, novel prognosticators, and introduction of targeted therapies. In recent years, a number of genetic profiling studies DS analyzing copy-number alterations as well as gene expression changes DS have deepened our understanding of STS development through demonstration of recurrently deregulated tumorigenic pathways. The challenge is now to bring the genetic profiles into clinical decision-making. This review, in conjunction with the Scandinavian Sarcoma Group's (SSG) 30 years jubilee, discusses how the information from genetic profiling studies may be translated into clinical practice for refined diagnostics, prognostics, and treatment of STS.